The Soviet Nordic Nuclear Weapon Free Zone Proposal - Lumsden, Catherine A. (1990)
This thesis examines the Soviet proposal and its ramifications for the United States and the West. The central theme running through each Soviet proposal has been removal of American nuclear guarantees. Preservation of US national security interests and hence US ability to extend its forward defense would be gravely threatened by such a NWFZ. However, unilateral agreement on a NWFZ is unlikely by the anticipated members of the Nordic NWFZ the US, USSR, Denmark, Norway, Finland, Iceland, Greenland, and Sweden. The US has military installations in Iceland and Greenland and banning of nuclear weapons during wartime is inconceivable. The question then arises as to which nation or groups of nations will dominate and which will acquiesce. Inevitably the debate breaks down to a tug of war between the two superpowers. It is really the politics surrounding the nuclear weapons that is the heart of the nuclear-free-zone debate. Changing world politics demand that the West develop a unified strategy toward the USSR. Through NATO it must preserve its vital economic political and military objectives in the Northern Flank. Flexible naval forces and strong political and economic ties to the governments of the nations bordering the Baltic are essential. Strong NATO naval forces operating in the Baltic Sea must be seen as guarantors of the West's strategic aims and interests. A Nordic NWFZ would prevent this.